EATING DISORDERS ARE ASSOCIATED WITH HYPEREMESIS GRAVIDARUM - Terävä-Utti, Eeva (My University, 2023)
Introduction: Hyperemesis gravidarum is a severe form of excessive vomiting during pregnancy. Although its etiology is considered multifactorial, the connection of psychiatric morbidity with HG has been discussed throughout the ages. Only a few studies have focused on the association between HG and eating disorders. The objective of the present study was to evaluate the association between HG and eating disorders using a large register-based data which consists of all first-time livebirths in Finland from 2005–2017. This study is also, to our knowledge, the first to investigate the association between HG and the new onset eating disorders after pregnancy. Material and methods: A retrospective register-based controlled study. Data of women with hyperemesis gravidarum diagnosis in Finland, 2005-2017, were retrieved from health care registers. Women who had diagnosed with hyperemesis gravidarum in their first pregnancy resulting in delivery were chosen as cases (n=6609, the HG group) and women with no hyperemesis gravidarum during the study period or earlier and who had their first pregnancy resulting in delivery as controls (n=188 362, the control group). First, associations between eating disorders and hyperemesis gravidarum were evaluated both before and after pregnancy. Second, the time interval between subsequent hyperemesis gravidarum pregnancies and postpartum eating disorders were observed as well as the cumulative effect of recurrent hyperemesis gravidarum on eating disorders. Results: A total of 1.48% of women with hyperemesis gravidarum and 0.28% of women without had pre-pregnancy eating disorder. Women with eating disorder had 5.4 times higher odds of getting an hyperemesis gravidarum in their first pregnancy resulting in delivery compared to women with no history of eating disorders. Conversely, a total of 0.32% of women with hyperemesis gravidarum and 0.11% of women without had eating disorder after pregnancy. Women with hyperemesis gravidarum had increased likelihoods of having eating disorder after pregnancy compared to women with no hyperemesis gravidarum diagnosis, although when previous psychiatric history was taken into account, the association between hyperemesis gravidarum and eating disorders after pregnancy disappeared. Conclusions: Hyperemesis gravidarum is associated with eating disorders both before and after pregnancy. Clinicians working with pregnant women with either hyperemesis gravidarum or eating disorder should pay attention on both diseases and the psychiatric evaluation is recommended at an early stage.
Keywords: eating disorder, hyperemesis gravidarum, nausea, vomiting, pregnancy, woman